A Transferência de Recursos Públicos no Município de São Paulo para a Rede Parceira da Educação Infantil e a Visibilidade desta movimentação junto às Mídias - SANTOS, SELMA ZEFERINO MACEDO DOS SANTOS (2019)
This research was developed under the research line Educational Policies and Management of the Stricto Sensu Graduate Program in Education (GPE, PPGE in Portuguese) of the Methodist University of São Paulo (MUSP, UMESP in Portuguese ) and has the support of the Coordination for the Improvement of Higher Education Personnel (CAPES), having as object of investigation the visibility in the media of the financing policy of daycare centers/nurseries in the municipal network of São Paulo, which allocates public funds to the indirect and private partner network, which has been characterized as a privatization movement of teaching. In this scenario, the research problematized such a policy by elaborating the following questions: I) Are data on the financing of daycare centers/nurseries available to the population, considering the law that guarantees the full knowledge and monitoring of society regarding budget and financial execution? II) Has this policy of transferring resources to the private partner network been publicized by the media for public knowledge? We assume that topics not covered by the media are not in the public sphere. To discuss these issues, public funds transferred to the network of partner private daycare centers/nurseries in São Paulo City Hall (SPCH, PMSP in Portuguese) were mapped, based on the survey of expenditures by the Municipal Education Secretariat (SME) in the economic category 3.3.50.39 - Transfer Private Non-Profit Institutions - in the municipality's budget executions, from 2015 to 2018, to identify which institutions have received the largest transfers and how these data are discussed by the media. This is an investigation that has two developments, one of document analysis (Cellard) in relation to funding and another of content analysis (Bardin) in relation to the media. The first development is based on the financing of education by mapping the values contained in the budget, which allocates public funds to the private partner network, and may subtract from children the fundamental right to an education based on the principles of the Federal Constitution (FC) of equal conditions, pluralism of ideas, democratic management of public education and guarantee of quality standard. For data collection, it was used to consult the pertinent legislation at the federal and municipal level, as well as the data contained in the PMSP website through the SME Portal, the Municipal Finance Secretariat (SF) and the Transparency Portal. The analyzes were based on the academic productions of Adrião, Domiciano, Franco, Gouveia and Souza, Pinto and Saviani. The second development referred to the data obtained from the Media, through the newspapers Folha de S.Paulo and Estadão, with large local circulation, verifying if public visibility of these data were their target, based on the principle of the right of the population to have access to information as a way to follow the decisions made by those who took over the public administration, given the deliberative potential of the Media in formulating Public Opinion, according to Habermas concepts that underlie researchers in the area. The methodology used for both moments is based on an exploratory and descriptive analysis. The research concluded that networks of private daycare centers/nurseries are being formed with public money and that there is no visibility of the theme with the media, which makes the participation of the population in the debate of this policy difficult.